Die Menschen hinter den Büchern: Beobachtungen aus der Handschriftenkatalogisierung der ZHB Luzern. - Führer, Dörthe (Jahrbuch der Historischen Gesellschaft Luzern, 2025)
The article discusses the special collection of the Central and University Library of Lucerne, which contains a group of manuscripts from the 16th and 17th centuries written by monks of the Cistercian monastery of St. Urban. These lecture notes, written in Latin, provide insights into the daily lives and thoughts of the writers through personal annotations and doodles. The manuscripts document the education of the monks, which was often associated with high financial costs, and highlight the significance of Aristotelian philosophy in the teaching of that time. The cataloging of the manuscripts is expected to be completed by 2025 to ensure comprehensive digital availability.